Multiple sleep dimensions and type 2 diabetes risk among women in the Sister Study: differences by race/ethnicity. Issue 1 (20th September 2019) - McWhorter, Ketrell L; Park, Yong-Moon; Gaston, Symielle A; Fang, Kacey B; Sandler, Dale P; Jackson, Chandra L
Abstract : Objective: Poor sleep has been associated with type 2 diabetes. Since racial/ethnic minorities experience a disproportionately high prevalence of poor sleep and type 2 diabetes, we sought to determine the relationships between multiple sleep dimensions and incident type 2 diabetes and to investigate if these relationships vary by race/ethnicity. Research design and methods: Prospective data were analyzed from the Sister Study, which enrolled 50 884 women from 2003 to 2009. Participants self-reported sleep duration, sleep latency, night awakenings, and napping at baseline, and a physician's diagnosis of type 2 diabetes at follow-up. Multivariable-adjusted HRs and 95% CIs were estimated using Cox proportional hazards models. Results: Among the 39 071 eligible participants, 87% self-identified as white, 8% black and 5% Hispanic/Latina. The mean follow-up period was 8.5±2.1 years and 1785 type 2 diabetes cases were reported. The incidence rate per 1000 person-years was 5.4 for whites, 13.3 for blacks and 11.6 for Hispanics/Latinas. There was a positive but non-significant increased risk of type 2 diabetes among women who reported short sleep, latency >30 min and frequent night awakenings. In fully-adjusted models, frequent napping was associated with a 19% (HR 1.19, 95% CI 1.04 to 1.37) higher type 2 diabetes risk in the overall sample. Poor sleep among racial/ethnic minorities ranged from a 1.4-fold to a 3.2-fold higher type 2 diabetes risk than whites with recommended sleep. Conclusions: Frequent napping was associated with higher type 2 diabetes risk. Racial/ethnic minorities with poor sleep had a higher type 2 diabetes risk than whites with recommended sleep.